The Rainbow Sky An Exploration of Colors in the Solar System and Beyond - Buick, Tony (The Patrick Moore Practical Astronomy Series, 2010)
The world is full of color, from the blue ocean and the yellow daffodils and sunflowers in green carpeted meadows to the majestic purple mountains in the distance and brightly hued coral reefs off the edges of tropical coasts. But what is color, exactly? Why do we see things in different colors? Do we all see the same colors? Like the surface of our planet, the sky above us offers us an endless palette of color, a visual feast for the eyes. Besides atmospheric phenomena such as sunsets and rainbows, there are the many varied worlds of the Solar System, which we can spy through our telescopes, with their subtle colorings of beige and blue and green. Faraway star systems have suns that come in shades ranging from red and yellow to blue and white. Scientists even often use "false colors" to enhance the features of images they take of structures, such as the rings of Saturn and Jupiter's clouds. This book, with its clear explanations of what makes the sky such a colorful place and in its great wealth of pictures, dazzles and delights while informing. Learn what makes the sky blue and our Sun yellow. Learn about all the quirky atmospheric events that color our world. And finally, learn how to see, really see, what's around you and appreciate and enjoy it.